Tindakan Sosial Pelaku Kesenian Damarwulan di Desa Sebemban - Novita, Winda; Vivian, Yofi Irvan; Setyoko, Aris (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
Damarwulan art is a traditional art originating from Java and developed by the people of Sebemban Village, Kutai Kartanegara Regency. The lack of interest in Damarwulan by the people of Sebemban Village has resulted in social action by cultural actors to protect this art. The sustainability of Damarwulan art to date cannot be separated from the social actions of its artists. There is music and scripts that have not changed from the past until now. This research uses qualitative methodology by applying observation techniques, data collection and data analysis. The observation technique includes the research object, namely focusing on damarwulan art in Sembemban Village. Data collection techniques include literature study, determining informants, interviews, and documentation. The final step is to use analytical techniques to process field data. The results of this research will explain the facts found in the field by the author. The social actions of Damarwulan artists towards the sustainability of this art include traditional, instrumental rational and value rational actions. Traditional acts include aspects such as rituals, male performers, scripts, and musical forms that have been passed down through generations. Instrumental rational action includes the use of musical instruments and other equipment in performance. Meanwhile, value rational actions involve collaboration with village government, extracurricular activities at schools, and arts groups as an effort to ensure the sustainability of Damarwulan Arts.